Решить формулы корней квадратного уравнения:

1)

(4х-5)^2-(2x+3)^2=0

2)

(x^2+4x+11)^2=(7x^2+2x+3)^2

2

Ответы и объяснения

2013-02-13T16:06:02+00:00

1) 

(4x-5)^2-(2x+3)^2=(4x-5+2x+3)*(4x-5-2x-3)=(6x-2)*(2x-8)=0

6x-2=0

x=1/3

2x-8=0

x=4

 

2)(x^2+4x+11+7x^2+2x+3)(x^2+4x+11-7x^2-2x-3)=(8x^2+6x+14)(-6x^2+2x+8)=0

8x^2+6x+14=4x^2+3x+7=0

D=9-112<0 решения нет

 

-6x^2+2x+8=3x^2-x-4=0

D=1+48=49

x1=(1+7)/6=4/3

x2=(1-7)/6=-1

2013-02-13T16:24:47+00:00

1) (4x-5)^2-(2x+3)^2=(4x-5+2x+3)*(4x-5-2x-3)=(6x-2)*(2x-8)=0

6x-2=0

x=1/3

2x-8=0

x=4

Отв: 1/3;4

 2)(x^2+4x+11+7x^2+2x+3)(x^2+4x+11-7x^2-2x-3)=(8x^2+6x+14)(-6x^2+2x+8)=0

8x^2+6x+14=4x^2+3x+7=0

D=9-112<0 решения нет

 3)-6x^2+2x+8=3x^2-x-4=0

D=1+48=49

x1=(1+7)/6=4/3

x2=(1-7)/6=-1

 Отв: 4\3;-1